2010
DOI: 10.5551/jat.2097
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-Ankle Pulse Wave Velocity Predicts Silent Cerebrovascular Diseases in Patients with End-Stage Renal Diseases

Abstract: Aim: Cerebrovascular disease (CVD) is a major determinant of the prognosis in end-stage renal diseases (ESRD). The purpose of this study was to examine whether factors associated with arterial stiffness contributed to the development of CVD in patients with ESRD. Methods: CVD (lacunes and carotid/intracranial artery stenosis) was evaluated with brain magnetic resonance imaging (MRI), and carotid/intracranial artery magnetic resonance angiography (MRA) in 44 pre-dialytic patients. The severity of CVD was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…To our knowledge, this is the first cohort study to show the impact of ADIPOQ G276T on prognoses and to suggest a mechanism of how ADIPOQ G276T affects the onset of stroke. Previous studies reported the correlation between PWV and silent cerebrovascular diseases 38) or insulin resistance 39) , and our results supported and provided new insight into these correlations.…”
Section: Discussionsupporting
confidence: 77%
“…To our knowledge, this is the first cohort study to show the impact of ADIPOQ G276T on prognoses and to suggest a mechanism of how ADIPOQ G276T affects the onset of stroke. Previous studies reported the correlation between PWV and silent cerebrovascular diseases 38) or insulin resistance 39) , and our results supported and provided new insight into these correlations.…”
Section: Discussionsupporting
confidence: 77%
“…PWV is a predictor of cardiovascular outcome in HD patients 23,24) . Washida et al have recently reported that arterial stiffness constitutes a novel determinant that predicts the severity of CVD in patients with ESRD in addition to the classical risk factors, and they have shown lower serum albumin levels and higher serum CRP levels in HD patients with severe lacunes 25) . Evidence has shown that atherosclerosis reflects the vascular inflammatory process 26) .…”
Section: Discussionmentioning
confidence: 99%
“…A lesion was defined as significant if it caused 50% reduction of the luminal diameter by visual estimation in vessels ≥ 1.5 mm. Each coronary lesion was separately scored and added to each coronary vessel to provide the vessel SYNTAX scores, which were then summed to provide the overall patient SYNTAX score, as previously described 13,14) , chial-ankle PWV (baPWV) has become available as a means of measuring PWV [7][8][9][10] . BaPWV can be obtained simply by wrapping the four extremities with blood pressure cuffs, and it has been suggested that this automatic, non-invasive device has the potential to be a simple marker of vascular damage severity 7) .…”
Section: Syntax Score and Angiographic Analysismentioning
confidence: 99%